PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Putri Ramadhani Azzachra (2022)
This study aims to analyze the effect of Profitability, Liquidity, and Firm Size on firm value with Dividend Policy as a moderating variable. The sampling technique used Purposive Sampling to obtain 13 Food and Beverage companies listed on the Indonesia Stock Exchange in 2018-2021. The data analysis technique uses Panel Data Regression and Moderated Regression Analysis (MRA) with the help of the Eviews 12 program. The results show that (1) Profitability has a positive effect on firm value, (2) Liquidity has no effect on firm value, (3) Firm size has an effect negative to firm value, (4) dividend policy moderates (strengthens) profitability to firm value, (5) dividend policy does not moderate liquidity to firm value, and (6) dividend policy moderates (weakens) firm size to firm value.